Jerusalem quarterly - Institute of Jerusalem Studies (Jerusalem Institute of Jerusalem Studies, 1998)
The Jerusalem Quarterly is the only journal that focuses exclusively on the city of Jerusalem's history, political status, and future. It addresses debates about the city and its predicament, as well as future scenarios for solving the problems of Jerusalem.
Previous title : Jerusalem quarterly file (#7 - 21, 2000-2004)
Keywords: History; HISTORY; JERUSALEM; ARAB-ISRAELI CONFLICT; PERIODICALS